2003
DOI: 10.1034/j.1600-0897.2003.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Immunoglobulin Treatment on the Th1/Th2 Balance in Women with Recurrent Spontaneous Abortions

Abstract: Our finding suggests that IvIg administration in women with alloimmune RSA enhances Th2 polarization. This is not always the case with APA-associated abortions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Stress-induced loss is mouse strain specific, and a similar genetically determined susceptibility most likely applies to humans as stress does not normally lead to loss of unwanted pregnancies (69). However, a common theme in patients with IVF failure/infertility and/or recurrent miscarriages has been increased NK activity,t increased Th1/Th2 cytokine ratios, and presence of autoantibodies, and patients undergoing IVF have an increased miscarriage rate which, from Table I, appears to be countered by IVIG (12,26,27,29,30,(44)(45)(46)(47)60,61,70). Freshly isolated allogeneic (paternal) leukocytes that can prevent spontaneous abortions in appropriately selected patients do not appear effective in preventing losses at the occult stage (before 6 weeks gestation) (13), and in a mouse model of stress-triggered loss, paternal leukocytes have proven ineffective (71,72).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Stress-induced loss is mouse strain specific, and a similar genetically determined susceptibility most likely applies to humans as stress does not normally lead to loss of unwanted pregnancies (69). However, a common theme in patients with IVF failure/infertility and/or recurrent miscarriages has been increased NK activity,t increased Th1/Th2 cytokine ratios, and presence of autoantibodies, and patients undergoing IVF have an increased miscarriage rate which, from Table I, appears to be countered by IVIG (12,26,27,29,30,(44)(45)(46)(47)60,61,70). Freshly isolated allogeneic (paternal) leukocytes that can prevent spontaneous abortions in appropriately selected patients do not appear effective in preventing losses at the occult stage (before 6 weeks gestation) (13), and in a mouse model of stress-triggered loss, paternal leukocytes have proven ineffective (71,72).…”
Section: Discussionmentioning
confidence: 92%
“…1 and Tables II and III notwithstanding), IVIG does downregulate NK activity in vivo as well as in vitro, and also can cause a ↓Th1/↑Th2 shift in cytokine production including increased production of GM-CSF that has been linked to improved implantation. (44)(45)(46)(47)(48)(49). Moffet et al (31) expressed concern about reproducibility of NK assays, but it may be intermittent peaks of NK activity rather than the steady-state average level that is important.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although most of these mechanisms were derived from in vitro work or animal models, some clinical studies confirmed that IVIg could decrease the Th1/Th2 ratio in the CD4 ϩ T-cell population [9][10][11][12] of treated patients or promote induction of Th0 or Th2 anti-inflammatory responses. [13][14][15] Such modulations of T-cell populations and of their cytokine secretion pattern could therefore contribute to the overall anti-inflammatory effects of IVIg by interfering with the pathogenic loop of continuous stimulation occurring in autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Polyclonal IgG has profound effects on both T and B lymphocytes, the key cellular components of the adaptive immune system. It may skew peripheral blood T cell subsets in multiple beneficial ways, including suppression of pro-inflammatory Th17 cells [25][26][27], promotion of protective CD4/CD25/FoxP3-positive T regulatory cells [28][29][30][31][32], induction of a protective Th1/Th2 shift [33][34][35], and inhibition of CD8-positive cytotoxic T cell activation and expansion [36,37]. Importantly, polyclonal IgG may inhibit T cell interactions with antigen-presenting cells by binding to T cell surface receptors, including the T cell receptor b-chain, HLA molecules, and costimulatory molecules such as CD28 [38][39][40][41].…”
Section: Reviewmentioning
confidence: 99%